2018
DOI: 10.1002/anie.201800037
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Phase Transfer of Carbon Dots between an Organic Phase and Aqueous Solution Triggered by CO2

Abstract: Carbon dots (CDs) have attracted increasing attention in applications such as bio-imaging, sensors, catalysis, and drug delivery. However, unlike metallic and semiconductor nanoparticles, the transfer of CDs between polar and non-polar phases is little understood. A class of amine-terminated CDs is developed and their phase transfer behavior has been investigated. It is found that these CDs can reversibly transfer between aqueous and organic solvents by alternatively bubbling and removing CO at atmospheric pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 60 publications
4
40
0
Order By: Relevance
“…This approach opens new synthetic opportunities via tailored CD synthesis or post-functionalization protocols and enables advanced applications such as catalytic transformations. [20][21][22][23][24] In particular, the appeal of CDs as nano-catalysts relate to their straightforward synthesis, cost-efficiency, and safety that, combined with high solubility in water, may allow their use even in biological or quasi-biological environments. [25][26][27][28][29] Despite their high potential, only exploratory applications of CDs as…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach opens new synthetic opportunities via tailored CD synthesis or post-functionalization protocols and enables advanced applications such as catalytic transformations. [20][21][22][23][24] In particular, the appeal of CDs as nano-catalysts relate to their straightforward synthesis, cost-efficiency, and safety that, combined with high solubility in water, may allow their use even in biological or quasi-biological environments. [25][26][27][28][29] Despite their high potential, only exploratory applications of CDs as…”
Section: Introductionmentioning
confidence: 99%
“…ll catalysts have been reported relying on simple acid-base or hydrogen-bonding activation modes. [20][21][22][23] Aminocatalysis represents one of the most versatile strategies in covalent organocatalytic transformations. The robustness of its activation modes, via enamine or iminium-ion intermediates, has been implemented in several synthetic applications addressing the requirements of step economy and metal-free catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…For all these reasons, the "bottom-up" approach is usually the preferred route for preparing catalytically active carbon nanoparticles. 25,26,[40][41][42] Besides, it has been shown that hetero-doping may enhance the photophysical and electronic features of CDs, by generating new energy levels and promoting radiative combination, therefore facilitating the process of designing and customizing of effective nanostructured photocatalysts. 1,4,5 One of the most important examples of doping is the widely investigated nitrogen incorporation, leading to the preparation of N-doped-CDs.…”
Section: Synthesis and Propertiesmentioning
confidence: 99%
“…The superficial carboxylic acid, hydroxy, or amino functionalities were exploited in acid-base, hydrogen bond, or amine-catalysed reactions. [12][13][14][15] CDs are also promising metal-free photocatalysts for pollutant degradation, H 2 evolution and CO 2 conversion, owing to their photostability, light-harvesting ability and electron-transfer efficiency. [16][17][18][19] The high solubility of CDs in water makes them a suitable alternative to hydrophobic organic materials, such as carbon nitride and graphite.…”
Section: Introductionmentioning
confidence: 99%